Application of maggot in ornamental fish culture - I Wayan Subamia; Yogi Himawan (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Maggot is one of alternative food source that potential to develop. At present, technique 0f culture of maggot can be done especially using media of Palm Kernel Meal (PKM). Application of maggot conducted in form of live food, freeze, and meal Application of maggot have been done for several commodity of ornamental fish especially in Center of Research and Development ofOrnamental Fish Aquaculture. Research using aquarium in indoor and conicle tank at outdoor.. Aplication maggot to the ornamental fish such as Gurame padang (Osphronemus gouramy), Rainbow Kurumoi (Melanotaenia parva), Botia (Chromobotia macracanthus), and Red cherry shrimp (Neocaridina heteropoda) results average of final weight and total length respectively 241,27 g and 18,26 cm ; 15,23 g and 24,06 cm ; 1,8 g and 4,9 cm ; 0,035 g and 0,03 cm. Meanwhile, survival rate of all ornamental fish in that research achieve 100%. Water quality parameter in that research still in good condition. Base on results of research, maggot give the positive effect to the growth and survival rate off all ornamental fish that tested